Exploring the convergence of computer and medical science through cloud healthcare - Queirós, Ricardo 1975-; Cunha, Bruno 1992-; Fonseca, Xavier 1987- (IGI Global, 2023)
With digital technologies currently dramatically changing healthcare, this book introduces the reader to the latest digital innovations in the cloud IoT health field and enumerates new methodologies and strategies in patient care.
Keywords: Medical technology